2023
DOI: 10.1002/jdd.13389
|View full text |Cite
|
Sign up to set email alerts
|

Gender trends in dentistry: Dental faculty and academic leadership

Aram Kim,
Nour Karra,
Crystal Song
et al.

Abstract: ObjectivesGender equality in the healthcare workforce has been a topic of discourse for many decades. In dental academia, women's representation of enrolled students and faculty has risen consistently since the 1980s. However, women in faculty leadership positions may still be lagging when compared to men. The purpose of this study was to evaluate the number of women who occupy the upper echelons of academic rank and title by analyzing cross‐referenced data from the American Dental Association and the American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The study respondents also expressed a significant increase in their desire to hold administrative positions, possibly due to increased representation of women in these roles at dental schools 4,5 One respondent explained: “ I think that having more women in dental education and in leadership/administrative roles makes visualizing opportunities for women by women more of the norm for current and upcoming generations ”.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The study respondents also expressed a significant increase in their desire to hold administrative positions, possibly due to increased representation of women in these roles at dental schools 4,5 One respondent explained: “ I think that having more women in dental education and in leadership/administrative roles makes visualizing opportunities for women by women more of the norm for current and upcoming generations ”.…”
Section: Discussionmentioning
confidence: 97%
“…Various studies have explored gender disparities in academic dentistry and have identified that women faculty experience reduced academic productivity, delays in promotion, and poor retention—but, why? 4–8 This discussion will focus on elevating the perspectives and lived experiences shared by women dental faculty in this study to better understand the drivers of gender inequities in dental education. Further, recommendations from women dental academics will be shared to highlight actionable ways in which barriers to career advancement can be dismantled and the aspirations of women in academic dentistry can be better supported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations